Fox (Vixen) and Wolf (She-wolf) in interpretation of Ukrainian folk fairy-tales in XIX century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The interpretational particularities of traditional tales’ characters as Fox (Vixen), Wolf (She-wolf) are reflected in this article. Authors’ features of their creatures are also analysed.
Keywords: tale; folk tale; fairy tale; literary tale; comparative constructions; zoonyms